2013
DOI: 10.1113/jphysiol.2013.252544
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid attenuates colonic epithelial secretory function

Abstract: Key points• Although diarrhoeal diseases represent a significant health and economic burden to society, therapeutic options remain limited.• While several bile acids are known to stimulate epithelial Cl − secretion, the major driving force for fluid secretion in the intestine, the effects of ursodeoxycholic acid (UDCA) on epithelial transport function are not well described.• We report that in contrast to other bile acids, UDCA exerts anti-secretory actions on colonic epithelial cells in vitro.• In contrast, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 40 publications
4
30
2
Order By: Relevance
“…As shown in Fig. 3D, and in contrast to the findings of Kelly et al (42), LCA did not change CCH-stimulated I sc in our T84 preparations. Therefore, for the remainder of the study, we probed the nature of the inhibition of cAMP-stimulated I sc by LCA, using FSK as the cAMP-dependent secretagogue.…”
Section: Lca Attenuates Responses To Only Camp-dependent Secretagoguecontrasting
confidence: 91%
See 1 more Smart Citation
“…As shown in Fig. 3D, and in contrast to the findings of Kelly et al (42), LCA did not change CCH-stimulated I sc in our T84 preparations. Therefore, for the remainder of the study, we probed the nature of the inhibition of cAMP-stimulated I sc by LCA, using FSK as the cAMP-dependent secretagogue.…”
Section: Lca Attenuates Responses To Only Camp-dependent Secretagoguecontrasting
confidence: 91%
“…Thus, they reported that LCA inhibits both basal-and carbachol (CCH)-stimulated I sc in rat distal colonic mucosa, stripped of underlying muscle within 10 min of addition (77). In contrast, in both stripped human colonic preparations and in T84 cells (42), they found that pretreatment with LCA (50 -250 M) for 15 min potentiates the action of CCH.…”
mentioning
confidence: 98%
“…This process must disrupt the epithelial barrier but neither the mechanism of the transepithelial passage nor any physiologic/pathophysiological consequences of this are well understood. S. mansoni, and other flukes (e.g., Clonorchis sinensis (human), Fasciola hepatica (cattle)), infect or affect the liver with implications for bile flow and bile salt formation: 47 bile acids can directly affect epithelial permeability and electolyte transport, 48,49 but we are unaware of data in support of the possibility that infection with these flatworms affect epithelial permeability indirectly via bile salts.…”
Section: Increased Epithelial Permeability Triggered By Infection Witmentioning
confidence: 99%
“…A third area not discussed is the role of bile acids in colonic secretion ( 447,448 ) and absorption ( 449 ), as well as recent work suggesting that bile acid activation of TGR5 is essential for normal defecation, at least in the mouse ( 70 ). Details of the biochemical mechanism(s) for bile acid-induced intestinal secretion are being elucidated by several laboratories, among these being that of Stephen Keely in Dublin ( 448 ), and that of Mrinalini Rao in Chicago ( 450 ).…”
Section: Topical Dissolution With Organic Solventsmentioning
confidence: 99%